A Case of Bilateral Frosted Branch Angiitis after mRNA COVID-19 Vaccination - Mai Kitaoka; Takako Ohnishi; Satoshi Sugaya; Harumasa Yokota; Taiji Nagaoka; Satoru Yamagami (Case Reports in Ophthalmology, 2023)
We report a case of bilateral frosted branch angiitis (FBA) following mRNA-1273 COVID-19 vaccination. A 79-year-old male was referred to our hospital with a sudden onset of blurred vision in the right eye, which occurred during his return home after receiving the third dose of a messenger RNA (mRNA) COVID-19 vaccine. Fundoscopy revealed severe retinal vasculitis with sheathing of the artery and vein in the right eye more so than in the left eye, suggestive of bilateral FBA. Optical coherence tomography showed significant macular edema and serous retinal detachment in the right eye. Polymerase chain reaction assay detected Epstein-Barr virus (EBV) in the aqueous humor, and antibody against the EBV viral capsid antigen was positive for IgM. The next day, best-corrected visual acuity (BCVA) worsened to 0.08 due to macular edema in the left eye. After 2 courses of pulse steroid therapy and intravenous infusion of acyclovir, macular edema had disappeared and sheathing of retinal vessels was improving. At 5 months after the mRNA COVID-19 vaccination, BCVA was maintained 0.15 in the right eye and 0.7 in the left eye. Severe uveitis, such as FBA, can occur after mRNA COVID-19 vaccination.